Cranial translation of the elevated prepuce in dogs before and after two modifications: A cadaveric study. Issue 7 (9th July 2021) - Yiapanis, Christos; Atamna, Raya; Gan El, Mirit; Shipov, Anna; Chochlios, Tryfon; Milgram, Josh
Abstract: Objective: To quantify cranial translation of the prepuce after elevating it from the ventral body wall and to compare it to the cranial translation achieved after each of two modifications expected to increase cranial translation. Study design: Cadaveric study. Sample population: Ten male dogs. Methods: All procedures were performed with dogs in dorsal recumbency. A urinary catheter with an attached millimeter scale was secured in the urethra and the penis was sutured to the ventral body wall to eliminate relative movement between the penis and prepuce. Three preplaced sutures between the prepuce and linea alba, at increasing distances from the prepuce, were used to translate the prepuce cranially. The prepuce was tested after elevating it from the ventral body wall, and after sequentially releasing the skin caudal to the prepuce (modification 1) and the attachment of the lamina interna to the penis (modification 2). The preplaced sutures were tightened and loosened sequentially from caudal to cranial, and the location of the dorsal aspect of the preputial opening on the millimeter scale was noted prior to, and after tightening each of the sutures. Results: Maximum mean (range) cranial translation of the prepuce after elevating the prepuce, and after modifications 1 and 2, was 15 mm (5–26 mm), 25 mm (15–30 mm), and 37 mm (24–50 mm), respectively. Conclusion: Modifications described increased cranial translation of the prepuce. Clinical significance: Modifications described in this study may provide alternate strategies for the treatment of dogs with severe paraphimosis.